2005
DOI: 10.1111/j.1365-2729.2005.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary school students' perceptions of interactive whiteboards

Abstract: Students involved in the interactive whiteboard (IWB) evaluation, sponsored by the Centre for British Teachers (CfBT), were interviewed in regard to their perceptions about IWBs. Twelve group interviews (72 students) were conducted between January and Easter 2004 with Year 6 students (between 10 and 11 years of age) in six Local Education Authority (LEA) areas located in the North and South of England. Students were very enthusiastic about particular aspects of IWBs, such as their versatility in the classroom,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
156
1
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(185 citation statements)
references
References 38 publications
10
156
1
14
Order By: Relevance
“…Throughout the study, teachers integrated numerous multimedia sources in their teaching, including: static images; Microsoft Encarta; Online sources such as governmental websites; Flash-based story books; PowerPoint Presentations; Microsoft Excel; and Geometer's Sketchpad. These findings are similar to those suggested by Hall and Higgins [7], who found this to be one of the major advantages of IWBs in learning environments cited by primary school students. In addition, we found that learners often referred to the fun and thought-provoking content when using the eBeam in the classroom.…”
Section: Teacher To Learnersupporting
confidence: 80%
See 2 more Smart Citations
“…Throughout the study, teachers integrated numerous multimedia sources in their teaching, including: static images; Microsoft Encarta; Online sources such as governmental websites; Flash-based story books; PowerPoint Presentations; Microsoft Excel; and Geometer's Sketchpad. These findings are similar to those suggested by Hall and Higgins [7], who found this to be one of the major advantages of IWBs in learning environments cited by primary school students. In addition, we found that learners often referred to the fun and thought-provoking content when using the eBeam in the classroom.…”
Section: Teacher To Learnersupporting
confidence: 80%
“…But when you teach without anything that would make them see, it becomes very difficult.' These findings are similar to previous research work where it was reported that the visual aspects of the IWB helped learners to understand content, making the teacher's explanations more effective [6,7,9,10,11]. Learners "most commonly associated the IWB with visual ways of learning.…”
Section: Teacher To Learnersupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, it is essential for particularly foreign language instructors to design a learner-centered, constructivist instructional environment in which students can actively use the IWB. In addition, overuse and misuse of the IWB by teachers may lead to a decrease on students' motivation and attention (Hall and Higgins 2005). Regarding this issue, one student commented that IWB make teachers job easier, they can use the existing materials on the board and do not have to lecture much.…”
Section: Teaching Turkish As a Foreign Language With Interactive…mentioning
confidence: 99%
“…Today, researchers from various disciplines are seeking alternative ways and solutions of using information and communication technology (ICT) to achieve more effective, interactive, and enjoyable instruction in schools (Hall and Higgins 2005;Smith et al 2005;Türel 2010). Interactive whiteboard (IWB), as an ICT, has been a growing trend to design more interactive learning environments in many disciplines including language learning (Tozcu 2008).…”
mentioning
confidence: 99%